An Approach for Data Hiding Technique Based on Reversible Texture Synthesis - Akhila Sreenivas, K; Babu, Pretty (International Journal of Computer Sciences and Engineering, 2025)
This paper proposes an improved method for steganography using reversible texture synthesis. Texture synthesis mechanism is the construction of large texture by using the input texture which is smaller in size. Combination of texture synthesis and steganography can provide better security and high embedding capacity than the existing method. Proposed method use location patch or header block to store the location of the embedded data. In the existing method the secret data was placed in source patches where as in the improved method the secret data is kept in blocks. Length of the embedding message is calculated which determines the required number of blocks needed for placing the message securely.